2007
DOI: 10.1051/forest:2007063
|View full text |Cite
|
Sign up to set email alerts
|

Effets de la densité de plantation sur la croissance et la qualité des bois dans un dispositif d’espacement de Populus xiaohei

Abstract: -The effect of stand density (1000 stems/ha, 500 stems/ha and 250 stems/ha) on tree growth and wood quality characteristics was studied in a 27-year-old plantation species of Populus xiaohei in China. Results indicated that stand density had significant effects on tree radial growth and crown size, and the lowest stand density produced trees with the largest stem taper. In terms of wood quality characteristics, there was no significant effect of stand density on either wood basic density or fiber length. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 21 publications
2
14
1
Order By: Relevance
“…In addition, the effect of planting density on some Persian maple stem features was quantified and tested. Previous studies have been reported on the variation of tree growth features, stand production, and wood characteristics under different iForest 9: 325-329 327 management strategies (Zobel & Van Buijtenen 1989, Jiang et al 2007, Naji et al 2014. We found that high PD had a more pronounced effect on tree growth rather than on wood properties.…”
Section: Discussioncontrasting
confidence: 38%
“…In addition, the effect of planting density on some Persian maple stem features was quantified and tested. Previous studies have been reported on the variation of tree growth features, stand production, and wood characteristics under different iForest 9: 325-329 327 management strategies (Zobel & Van Buijtenen 1989, Jiang et al 2007, Naji et al 2014. We found that high PD had a more pronounced effect on tree growth rather than on wood properties.…”
Section: Discussioncontrasting
confidence: 38%
“…The lower response of P. cembroides to drought suggested that it was more water efficient than P. engelmannii and better adapted to withstand prolonged water deficit. Additional factors such as stand density [22], neighborhood tree composition [23], and management history including thinning [23] could also affect our results. Management could partially explain some of the findings observed at the xeric habitat, which is managed with the selection system [28], whilst thinning seems to not be relevant in the protected mesic habitat.…”
Section: Discussionmentioning
confidence: 84%
“…Along with these gradients, radial growth (usually measured as changes in tree-ring width) varies in response to changes in water deficiency [5,18], site conditions [19], and tree characteristics (e.g., tree size, age, dominance, or vigor) [20,21]. Stand density [22], neighborhood composition [23], and past management history including thinning regimes [24] may also affect trees' responses to drought.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no practical examples reported. The frequency of discolored wood and stem number has been studied on Populus xiaohei by Jiang et al [35]. In their studies, the proportion of wetwood at DBH increased from 60% to 68.1% in stands with 1000 and 250 stems ha −1 respectively.…”
Section: Characteristics Of the Distribution Of False Heartwood In Stemsmentioning
confidence: 99%